ORGANOLEPTIC FEED VALUE OF FERMENTED LITTER BROILER-BASED SUPPLEMENT CELLULOSELYTIC BACTERIAL ISOLATE OF BALINESE PIG ORIGIN - K. Y. A., PARTAMA; MUDITA, I M.; WIRAWAN, I W. (Majalah Ilmiah Peternakan, 2025)
The aim of this research is to determine the organoleptic value of broiler litter-based supplement feed fermen- ted with cellulolytic bacterial isolates from Bali pigs. The research was conducted from January-March 2024 at Udayana University, Animal Nutrition and Forage Laboratory, Faculty of Animal Husbandry. This study used a completely randomized design (CRD) which included 4 replications and 4 treatments. The treatments distributed were feed supplements fermented using only water as a control (A), Bacillus licheniformis isolates (B), Bacillus lentus isolates (C) and combination isolates (Bacillus licheniformis and Bacillus lentus) (D). The variables studied included aroma, color, presence of mold and texture. The results of this research show that treatment (D) provides the highest scoring on the variables of aroma, color, presence of mold and texture. It can be concluded that broiler litter-based supplement feed which is fermented using a combination of isolates, namely Bacillus licheniformis and Bacillus lentus (D), produces supplement feed that has good quality color, aroma, texture and the presence of fungi.